MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION BERBASIS ASSESSMENT FOR LEARNING PADA PERSAMAAN GARIS LURUS DITINJAU DARI KARAKTERISTIK CARA BERPIKIR - Naning Sutriningsih, author (JURNAL E-DUMATH, 2015)
The aims of this research are to find out the different effect of each categories of cooperative learning model, characteristics of mind style and their interaction towards students mathematics learning results on equation of straight line. The research used to quasi experimental with 2x4 factorial design. The population was all of the students in Grade VIII of the State Junior High Schools of the district Pringsewu in academic year 2013-2014. The samples of the research were taken by stratified cluster random sampling technique. Based on hypothesis test, it can be conclude that: 1) the cooperative learning model of TAI type on the basis of the AfL gives a better mathematics learning results than TAI type; 2) the mathematics learning result of student abstract sequential (AS) type have a better than student concrete sequential (CS) type, student concrete random (CR) type, and student abstract random (AR) type; whereas student CS type have the same result of student CR type and student AR type; 3) at each of characteristics of mind style students (CS, AS, CR. and AR), the cooperative learning model of TAI type on the basis of the AfL gives a better mathematics learning results than TAI type.Keywords: Team Assisted Individualization (TAI), Assessment for Learning (AfL), The Characteristics of Mind Style, Learning Result in Mathematitcs.